197k views
2 votes
Please hurry i need help please

Please hurry i need help please-example-1
User Slaporte
by
6.0k points

1 Answer

4 votes

Answer:

(x-3)(x-7)

Explanation:


f(x) = x {}^(2) - 11x + 24 \\ g(x) = x - 3 \\ f (x) - g(x) = x ^(2) - 11x + 24 + x - 3 \\ collect \: like \: terms \\ f - g(x) = x ^(2) - 11x + x + 24 - 3 \\ f - g(x) =x ^(2) - 10x + 21 \\ f - g(x) =x ^(2) - 3x - 7x + 21 \\ f - g(x) =x(x - 3) - 7(x - 3) \\ f - g(x) =(x - 3)(x - 7)

  • hope it helps
User Punstress
by
5.9k points